Pengaruh Berat Cacing African NightCrawler (Eudrilus Eugeniae) Terhadap Sifat Fisik Vermikompos Feses Sapi - Isnaeni, Nurul (CV. SINAR HOWUHOWU, 2026)
Vermicomposting is an organic waste processing technology using earthworms and microorganisms to produce high-quality organic fertilizer. This study aims to determine the effect of differences in the weight of African Night Crawler (ANC) worms on the physical properties of vermicompost made from cow feces. The study used a Completely Randomized Design (CRD) with four treatments: V1 (20 g), V2 (40 g), V3 (60 g), and V4 (80 g) ANC, with five replications. The parameters observed included water content, temperature, humidity, color, odor, and texture. The results showed that differences in worm weight did not have a significant effect (p>0.05) on all physical properties of vermicompost. The color of the vermicompost in all treatments was slightly black, had an earthy odor, and had a slightly smooth texture as an indicator of compost maturity. The final compost temperature was in the range of 27–28°C, while the final humidity was in the range of 50–60%. The moisture content of vermicompost ranged from 59–68%. It can be concluded that the difference in ANC weight does not affect the physical properties of vermicompost, even though all results have met the compost maturity indicators.